Optimization of Black Garlic Protein Extraction Process and Exploration of Its Properties and Functions with Enzymatic Hydrolysis Products - Jian Liu; Yuanyuan Wang; Bo Wang; Wei Zhang; Xiaoyu Ren; Youchuang Zhang; Lijun Jiang; Chunming Dong; Guihong Zhao (Molecules)
This study optimized the process of extracting protein from black garlic using an alkaline dissolution and acid precipitation method through response surface methodology. The optimal extraction conditions were determined as a solid-to-liquid ratio of 1:50, an extraction time of 100 min, an extraction temperature of 30 °C, and an alkaline extraction pH of 9.0. Under these optimized conditions, the actual black garlic protein (BGP) extraction yield was 12.10% ± 0.21%, and the isoelectric point of the obtained BGP was 3.1. Subsequently, this study extracted black garlic protein under optimal conditions and subjected it to enzymatic hydrolysis using different enzymes (trypsin, pepsin, and their mixed enzymes). The functional characteristics, antioxidant activity, and hypoglycemic activity of black garlic protein before and after enzymatic hydrolysis were compared. Among the hydrolysates, the pepsin hydrolysate (BGPH-P) had the smallest particle size (188.57 ± 1.93 nm) and the highest Zeta potential (−29.93 ± 0.42 mV). Scanning electron microscopy showed that BGPH-P had the smallest and most dispersed particles. Fourier-transform infrared (FTIR) spectroscopy revealed that the dual enzymatic hydrolysis hydrolysate (BGPH-PT) exhibited the most stable structure. Compared to BGP, the hydrolysates demonstrated significantly improved solubility, water-holding capacity, and foaming ability (p < 0.05), while their emulsifying activity, emulsion stability, DPPH radical scavenging capacity, and hypoglycemic activity decreased. In summary, the BGP extracted using the optimized process demonstrated good antioxidant and hypoglycemic activities, while its enzymatic hydrolysate BGPH-P exhibited excellent solubility, water-holding capacity, and emulsifying properties, providing valuable insights for the further development of black garlic protein and its hydrolysates.